A meta‐analysis of the cumulative incidence, risk factors, and clinical outcomes associated with chronic kidney disease after liver transplantation. (15th November 2021) - Lim, Sze Yinn; Wang, Renaeta; Tan, Darren Jun Hao; Ng, Cheng Han; Lim, Wen Hui; Quek, Jingxuan; Syn, Nicholas; Nah, Benjamin Kai Yi; Wong, Emmett Tsz‐Yeung; Huang, Daniel Q.; Vathsala, Anantharaman; Siddiqui, Mohammad Shadab; et al.
Summary: Chronic kidney disease (CKD) remains a relatively common complication after liver transplantation (LT), and significantly impacts overall survival. We sought to assess the cumulative incidence, risk factors and mortality associated with post‐LT CKD. CKD was defined as eGFR <60 ml/min/1.73 m 2 as estimated by the Modified Diet in Renal Disease (MDRD) formula. Single‐arm meta‐analysis was done to evaluate the cumulative incidence of CKD at 1‐, 3‐, and 5‐year timepoints post‐LT. Risk factors for CKD were evaluated using hazard ratios (HR). Twenty‐one studies involving 44 383 patients were included. Cumulative incidence of stage 3–5 CKD was 31.44% (CI 0.182–0.447), 36.71% (CI 0.188–0.546), and 43.52% (CI 0.296–0.574) at 1, 3, and 5 years after LT, respectively. Stage 5 CKD cumulative incidence increased from 0.274% (CI 0.001–0.005) at 1 year to 2.06% (CI 0.009–0.045) at 5 years post‐LT. Age, female sex, diabetes, and peri‐operative acute kidney injury (AKI) were significant risk factors for CKD. Stage 4–5 CKD was associated with a decrease in overall survival (HR 3.23, 95% CI 1.74–5.98, P < 0.01). CKD after LT is relatively common, and is associated with significantly reduced overall survival. Identification of patients at high risk of developing CKD allows physicians to prophylactically use renal‐sparing immunosuppression which may be crucial in achieving desirable clinical outcomes. Abstract : Cumulative incidence of chronic kidney disease (CKD) increased from 31.44% at 1‐year to 43.52% at 5‐years after LT. Age, female sex, diabetes, and peri‐operative acute kidney injury were significant risk factors for CKD. Importantly, stage 4–5 CKD was associated with significantly lower overall survival (HR 3.23, 95% CI 1.74–5.98, P < 0.01).